Factors Affecting The Integrity Of Property And Real Estate Company Financial Statement - Leny Suzan; Rizaldi, Viola Rosselini (Fakultas Ekonomi dan Bisnis Universitas Tarumanagara, 2024)
Companies have a responsibility to uphold integrity when disclosing financial reports. This research examines Indonesian Stock Exchange-listed companies in the property and real estate subsector from 2017 to 2021, specifically focusing on the ownership structure of financial, leverage, and intellectual assets and their impact on the integrity of financial statements. Quantitative methods, including panel data regression and descriptive statistics, are used to test hypotheses. A purposive sampling technique was utilised, resulting in a sample of 16 companies and 70 observation data points. The results indicate that ownership by institutions, managers, financial leverage, and intellectual assets collectively impact the honesty of financial statements. According to the findings, leverage affects the integrity of financial accounts somewhat positively, whereas managerial ownership exerts an adverse impact. However, no significant influence was found between institutional ownership and intellectual capital in relation to financial statement integrity.